THE INFLUENCE OF STRESS AND PROCRASTINATION TOWARD STUDENT’S MOTIVATION THE FINAL PROJECT AT POLITEKNIK NEGERI SEMARANG - Rara Ririn Budi Utaminingtyas; Saptianing - Saptianing; Rif'ah Dwi Astuti; Rustono - Rustono (Politeknik Negeri Semarang, 2017)
ABSTRACTThe objectives of this study are 1) to know about student’s stress at business administration department who do final project and scription 2) to know student’s procrastination at business administration department 3) to analize the influence of stress and procrastination over all and partial toward student’s motivation at business administration department to finish final project and scription. Subjects of this study are students who arrange their final project at business administration study program (D3) , marketing management study program (D3) and International Business Management study program (D4). Data were collected by observation, interview, and questionnaire. Samples of this study are 60 students were selected by quota random sampling technique. Data were analized by multiple linear regression. Result of this study variable stress and procrastination have significant influence toward student’s motivation at business administration department Politeknik Negeri Semarang to finish final project and scription. Regression equation that obtained:Y = 4,237 – 0,234 (X1) + 0,223 (X2)Partially, stress has significant influence toward motivation of regression coefficient stress variable with the result is -0,234. It mean that If stress (X1) increases while other variable are consistant, so motivation will be decrease. Procrastination has significant influence toward motivation. The result of regression coefficient procrastination variable (X2) is 0,223. It mean that if procrastination increases while other variable are consistant, so student’s motivation to finish final project will be increase. The benefit of stress and procrastination variable toward variable Y (motivation) are r square ...0,107 or 10,7%. While 89.3% influenced by other variable that didn’t examined in this study. Keywords: Stres; Procrastination; MotivationABSTRAKTujuan penelitian ini adalah: mengetahui stress mahasiswa yang sedang menyusun tugas akhir atau skripsi; mengetahui prokrastinasi yang dialami mahasiswa yang sedang menyusun tugas akhir atau skripsi; dan menganalisa pengaruh stress dan prokrastinasi secara menyeluruh dan parsial terhadap motivasi mahasiswa menyusun tugas akhir dan skripsi. Subyek penelitian ini mahasiswa yang sedang menyusun Tugas Akhir program studi Administrasi Bisnis dan Manajemen Pemasaran (D3), dan program studi Manajemen Bisnis Internasional (D4) yang sedang menyusun Skripsi. Pengumpulan data dilakukan dengan observasi, wawancara, dan kuesioner. Sampel dalam penelitian ini adalah 60 mahasiswa tingkat akhir jurusan Administrasi Bisnis dipilih dengan teknik quota random sampling. Data dianalisis dengan regresi linear berganda.Hasil penelitian ini variabel Stress dan Prokrastinasi mempunyai pengaruh yang signifikan terhadap Motivasi mahasiswa jurusan Administrasi Bisnis Politeknik Negeri Semarang dalam menyelesaikan Tugas Akhir dan Skripsi. Persamaan regresi yang diperoleh Y = 4,237 - 0,234 (X1) + 0,223 (X2)Secara parsial Stress mempunyai pengaruh yang signifikan terhadap terhadap Motivasi Koefisien regresi variabel Stress (X1) sebesar -0,234, Berarti bahwa jika Stress (X1) meningkat 1 sedangkan variabel lainnya tetap (ceteris paribus), maka motivasi menurun. Pengaruh Prokrastinasi signifikan terhadap Motivasi Koefisien regresi variabel Prokrastinasi (X2) sebesar 0,223. Berarti bahwa jika Prokrastinasi (X1) meningkat 1 sedangkan variabel lainnya tetap (ceteris paribus), maka motivasi mahasiswa dalam menyelesaikan tugas akhir meningkat . Sumbangan variable X ( X1 stress dan X2 prokrastinasi) terhadap variable Y ( motivasi) adalah r kuadrat yang disesuaikan sebesar 0,107 atau 10,7%, sedangkan 89,3% lainnya dipengaruhi oleh variable lain yang tidak diteliti dalam penelitian ini. Kata kunci: Stress; Prokrastinasi; Motivasi